Структурно адаптивне морфологічне покращання зображень з використанням логарифмічних перетворень - Івасенко, І.Б. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
An adaptive image enhancement method based on logarithmic image processing is presented. Using of combination of logarithmic multiplicative operators with different structuring elements allows to enhance low contrast image fragments. Experimental results confirm effectiveness of generalized logarithmic image processing model and allow to select adaptive parameter of the method.